Identificación de las causas de accidentes de tránsito en el circuito Politécnica de la ciudad de Riobamba, Provincia de Chimborazo. - Carrasco Lara, Neiva Tamara (2023)
According to Antonio Guterres, Secretary General of the United Nations, "Road crashes are a silent and walking epidemic," road traffic injuries are the eighth leading cause of death worldwide, according to the general death registry of INEC in the year 2021 in the city of Riobamba, land transportation accidents are among the 10 leading causes of death. The purpose of this research work is to analyze the causes of traffic accidents in the Politécnica area, in the city of Riobamba, in order to be able to make a proposal using the Haddon matrix to avoid these accidents. According to data obtained from the Directorate of Traffic and Transportation Management on road accidents in 2019, 2020, 2021 and 2022, the main causes of traffic accidents are due to not respecting the distance between vehicles, recklessness or distraction of the driver and not respecting traffic signs. This research was carried out based on surveys, which were the support to identify the criteria that will be considered relevant at the time of studying the causes of traffic accidents. As a result of the research project, it was concluded that a large percentage of pedestrians walk on the sidewalks and spaces provided for pedestrians, however, they consider that these spaces are not safe. In addition, pedestrians believe that most traffic accidents occur due to drivers' disrespect for traffic laws. Drivers do not respect traffic laws since most of them exceed the established speed limits and even use their cell phones while driving.